VIOLENCE INTERVENTION PROGRAMME (VIP); IMPROVING NEW ZEALAND'S HEALTH SYSTEM RESPONSE TO FAMILY VIOLENCE. (7th October 2012) - Koziol-McLain, J; Ritchie, M; Zimmerman, S
Abstract : Background: The New Zealand Violence Intervention Programme (VIP) seeks to reduce and prevent health impacts of violence and abuse through early identification, assessment and referral of victims presenting to health services. The programme is premised on standardised system models of organisational change and reflects an indigenous whanau ora approach. Programme components include national guidelines, coordinators, technical advice, national networking, training, resources and evaluation. Aim: To describe the respective contributions of funders, national programme manager and researcher to the achievements of VIP within the health sector. Methods: National programme management and evaluation focuses on a coordinated approach to quality improvement. An external evaluation monitored development of VIP from 2004–2011 in 20 District Health Boards. The evaluation applied partner abuse (PA) and child abuse and neglect (CAN) programme audit tools measuring system indicators. Results: VIP scores increased incrementally over the six audit periods. Median audit score (possible range 0 to 100) increased from 20 to 74 for responsiveness to PA and from 37 to 81 for responsiveness to CAN. At the most recent audit (2011), 17 DHBs (85%) achieved the benchmark target score (>70) in both PA and CAN programmes, exceeding Ministry of Health expectations. Significance/Contribution to the Field: Longitudinal evaluations of national PA and CAN intervention programmes in health are limited. VIP design and external evaluation results provide evidence to guide future programme development. Recommended areas include transitioning programme evaluation from indicator compliance to a culture of continuous performance improvement and increasing provision of service delivery to families at risk.